The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.1002/jgm.3362
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of the analytical performance of non‐invasive prenatal testing (NIPT) in detecting sex chromosome aneuploidies: 34,717‐patient sample in a single prenatal diagnosis Centre in China

Abstract: Objective: The present study aimed to evaluate the efficacy of a non-invasive prenatal test (NIPT) in the detection of the sex chromosome aneuploidies (SCAs) at our prenatal diagnosis centre.Methods: Among a cohort of 34,717 pregnancies, maternal plasma samples from our prenatal diagnosis centre were subject to analysis of SCAs using NIPT detection.Pregnant women with NIPT positive results of SCAs were recommended to undergo an invasive prenatal diagnosis (i.e. karyotyping and fluorescence in situ hybridizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
3
11
0
Order By: Relevance
“…The PPV of NIPT in sex chromosomes trisomy was consistent with the report of Suo et al ( 2018 ) on 47,XXX, 47,XXY, and 47,XYY. The PPV of 45,X was consistent with the results reported by Kornman et al ( 2018 ), and was lower than those of which reported by Suo et al ( 2018 ), Persico et al ( 2016 ), Porreco et al ( 2014 ), Song et al ( 2013 ), and Luo et al ( 2021 ). The lower PPV of 45,X might also be related to the fact that a greater number of 45,X fetuses have abnormal ultrasonic structures than other types of SCA fetuses, so their parents tend to forgo diagnosis and proceed to the termination.…”
Section: Discussionsupporting
confidence: 90%
“…The PPV of NIPT in sex chromosomes trisomy was consistent with the report of Suo et al ( 2018 ) on 47,XXX, 47,XXY, and 47,XYY. The PPV of 45,X was consistent with the results reported by Kornman et al ( 2018 ), and was lower than those of which reported by Suo et al ( 2018 ), Persico et al ( 2016 ), Porreco et al ( 2014 ), Song et al ( 2013 ), and Luo et al ( 2021 ). The lower PPV of 45,X might also be related to the fact that a greater number of 45,X fetuses have abnormal ultrasonic structures than other types of SCA fetuses, so their parents tend to forgo diagnosis and proceed to the termination.…”
Section: Discussionsupporting
confidence: 90%
“…During the last decade, cfNIPT has been introduced worldwide as an efficient screening tool for detection of trisomies 13, 18, and 21 and potentially sex chromosomes, however, the positive predictive value for the SCAs is lower (Gadsbøll et al, 2020;Luo et al, 2021;Pertile et al, 2021). Prenatal diagnosis of SCAs in a fetus is complicated by the absence of confirmatory ultrasound findings beyond the increased nuchal translucency (Christiansen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the positive predictive value (PPV) for detection of 45,X by cfDNA screening is much lower than for trisomy 21, ranging from 9% to 40%, and various factors limit its performance. [20][21][22][23][24][25][26] Confined placental mosaicism (CPM) and true fetal mosaicism are more common for monosomy X than for other chromosomal abnormalities. 27 The performance of cfDNA testing for SCA can also be affected by undiagnosed maternal sex chromosome abnormalities, such as X-chromosome deletions or mosaic Xchromosome aneuploidy, including the well-described somatic maternal loss of the second X chromosome with increasing maternal age.…”
Section: Introductionmentioning
confidence: 99%